2019
DOI: 10.18332/tpc/113357
|View full text |Cite
|
Sign up to set email alerts
|

Smoke-free home initiative in Bantul, Indonesia: Development and preliminary evaluation

Abstract: INTRODUCTION Tobacco control policies in Indonesia are still limited. This study aims to describe the process of the implementation of the smokefree home (SFH) program in rural areas in Indonesia and to conduct a preliminary evaluation of its implementation. METHODS The development of SFH (or Rumah Bebas Asap Rokok) applies the theory of diffusion of innovation with the following stages: innovation, dissemination, adoption, implementation, and evaluation. The preliminary evaluation of the SFH program used an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Other suspected factors that could have reduced the effect size are possible remaining barriers, such as risk to routine harmonious social relationships in the community [66], which over 50% of male partners in both groups mentioned. As a next step, a community-wide intervention with supportive local leaders is recommended [67].…”
Section: Discussionmentioning
confidence: 99%
“…Other suspected factors that could have reduced the effect size are possible remaining barriers, such as risk to routine harmonious social relationships in the community [66], which over 50% of male partners in both groups mentioned. As a next step, a community-wide intervention with supportive local leaders is recommended [67].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in India and Nigeria showed that smoke-free workplaces are associated with a higher proportion of adults reporting a smoke-free home,[ 19 20 ] an initiative that is also currently lacking in Indonesia. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, household exposure to SHS remains a relevant risk factor and is significantly associated with lower birth weight, LBW, and smaller size at birth at population level in Indonesia. For the implementation of strategies to minimize SHS exposure, the home of non-smokers living with smokers must be taken into account through smoke-free homes policy (Trisnowati et al, 2019). Therefore, it is not only important to enact regulations, but also to consider more public health strategies to raise awareness of the adverse health effects caused by SHS exposure.…”
Section: Discussionmentioning
confidence: 99%